A Multicenter Experience With a New Fenestrated-Branched Device for Endovascular Repair of Thoracoabdominal Aortic Aneurysms. (April 2018) - Youssef, Marwan; Deglise, Sebastien; Szopinski, Piotr; Jost-Philipp, Schäfer; Jomha, Amer; Vahl, Christian F.; Koshty, Ahmed
Purpose: To investigate the outcomes of patients who were treated for thoracoabdominal aortic aneurysms (TAAAs) using custom-made fenestrated-branched stent-grafts.Methods: A consecutive series of 108 patients (mean age 73.5 years; 73 men) with TAAA were treated with E-xtra Design Engineering customized fenestrated-branched stent-grafts between November 2011 and January 2017. Data on baseline characteristics, procedures, and clinical follow-up were collected from 6 regional European surgical centers for retrospective analysis of endoleaks, reinterventions, and target vessel patency. The median aneurysm diameter was 6.75 cm (range 5.5–13). The distribution of the TAAA according to the modified Crawford classification of extent was 25 (24%) type I, 19 (17%) type II, 20 (18%) type III, 29 (27%) type IV, and 15 (14%) type V.Results: Technical success was achieved in 95% (103/108) of cases. Major early perioperative complications occurred in 40 (37%) patients. The 30-day mortality was 9.2% (10/108), and perioperative spinal cord ischemia was observed in 6 (5.5%) patients [2 (1.8%) permanent]. During the mean follow-up of 17.6 months (range 3–52), 28 (26%) patients required late reintervention. Two patients died due to aneurysm- or procedure-related causes. The estimated survival rates at 1, 2, and 4 years were 87%, 84%, and 51%, respectively. The estimated target vessel patency rates at the same time points were 95%, 91%, and 90%, respectively. The freedom from reintervention estimates were 84% and 73% at 1 and 4 years, respectively.Conclusion: Endovascular repair of TAAA using Jotec customized fenestrated-branched stent-grafts appears to be safe and effective in the early to midterm. The considerable rate of secondary interventions indicates that further improvements, graft surveillance, and follow-up are required.